4-Electrode Full Cells for Operando Li+ Activity Measurements and Prevention of Li Deposition in Li-Ion Cells. Issue 9 (27th April 2020) - Hogg, Björn-Ingo; Waldmann, Thomas; Wohlfahrt-Mehrens, Margret
Abstract : Li plating is a severe and safety relevant aging mechanism which has to be avoided. A new 4-electrode operando pouch full cell, with two Li reference electrodes is developed. The voltage shifts between the two Li metal electrodes are correlating directly with changes in the Li + activity a[Li + ] in the electrolyte in front of the anode surface. We take advantage of the Li + activity dependency of the Li + /Li redox potential as described by the Nernst equation to measure the Li + activity in the electrolyte. On this basis, the mismatch between reaction and transport kinetics in anode and cathode is discussed. Finally, optimized fast-charging procedures based on strictly positive anode potentials are deduced from the measurements in cells with reference electrodes. These charging protocols allow reducing charging time while enhancing cycle life significantly. The second reference electrode is helpful to understand these measurements in terms of Li + activity during charging. The applicability of such fast-charging protocols is demonstrated on the example of commercial 16 Ah pouch and lab cells.